Molecular and morphological evidences reveal two new species in Grammothele and Theleporus (Basidiomycota) from southern China - Yuan, Hai-Sheng (Phytotaxa, 2015)
Two new wood-decaying polypores from southern China, Grammothele separabillima and Theleporus rimosus, are described and illustrated using morphological characteristics and rDNA ITS sequences. Grammothele separabillima is characterized by its easily separable basidiocarps, poroid hymenophore with hymenium restricted to the base of the tubes, a dimitic hyphal system, pale brown skeletal hyphae with dextrinoid reaction, presence of dendrohyphidia, and oblong ellipsoid basidiospores. Theleporus rimosus is characterized by its resupinate, cracked basidiocarps, shallow poroid hymenophore with hymenium restricted to the base of the tubes, a di-trimitic hyphal system with dendroid and non-dextrinoid skeletal hyphae, presence of dendrohyphidia and ellipsoid to fusiform basidiospores. The discriminating characters of these two new species and the closely related species are discussed.